Docetaxel in very elderly men with metastatic castration-resistant prostate cancer - Wong, Hui-Li (Prostate Int, 2015)
PURPOSE: To evaluate the use of docetaxel in very elderly men with metastatic castration-resistant prostate cancer (mCRPC) treated in routine clinical care. METHODS: A retrospective case series of men with mCRPC aged ≥80 years and treated with docetaxel between July 2006 and June 2012 at three community hospitals in Melbourne, Australia. RESULTS: Twenty patients were identified, with a median age of 83 years (range 80–93 years). Aside from one patient treated weekly, all patients were treated with a 3-weekly regimen of docetaxel with a median of six cycles (range 1–10 cycles) delivered. Eight patients (40%) had an initial dose reduction and 11 patients (55%) had subsequent dose delays or reductions. Eight patients (40%) completed planned treatment. Grade 3/4 hematologic toxicity was observed in nine patients (45%), and five patients (25%) were admitted to hospital with chemotherapy-related complications. Prostate-specific antigen (PSA) response was assessable for 16 patients, of whom nine (56%) had a PSA response of ≥50% and one (6%) had a PSA-complete response. The median overall survival in this cohort was 13.4 months. CONCLUSIONS: Very elderly patients (80 + years) with mCRPC are infrequently included in clinical trials, yet the use of chemotherapy in this population is likely to increase. Our series demonstrates significant response rates to docetaxel chemotherapy, but that a substantial number of patients had treatment-related complications. This highlights the need for careful patient selection and optimization of chemotherapy dosing.